Dutch Lives. The Historical Sample of the Netherlands (1987−): Development and Research - Kees Mandemakers; Jan Kok (Historical Life Course Studies)
The HSN was initiated during the period 1987−1989 when an interdisciplinary and interuniversity group of Dutch scholars started discussing the foundation of one large database with data on individuals. Building one general prospective database with multiple research possibilities was considered as the only way to realize a cost-effective and properly documented tool for historical research from economic, social, demographic, epidemiological and geographic perspective. The birth registration was considered the most adequate sample framework. The new database should be 'open' in the sense that extension should be possible in all kinds of ways: more sources or variables, more persons and larger time periods. The HSN was deliberately created as a nationwide sample covering the whole 19th and 20th century. Since 1991 about 12 million Euro has been invested in the database and related projects. Besides the basic sample about 25 additional projects have been realized that created all kind of extensions to the database. A special project is LINKS by which the indices of names from the Dutch civil registration are used to reconstruct pedigrees (for the period 1780−1940) and complete families (1811−1900) for the whole of the Netherlands or parts of it. In this article we will present an overview of the research that was done with the original themes and the new fields that were introduced over the years. We will also go into methodological issues that were picked up by the 'HSN community' and we will point out the present and future challenges for the HSN.